«Amaos y no os multipliquéis». El discurso ético-sexual del anarquismo individualista en Cataluña, (1927-1937) (Spagna contemporanea. Rivista semestrale di storia, cultura, istituzioni, 2002)
«Amaos... y no os multipliquéis». El discurso ético-sexual del anarquismo individualista en Cataluña, (1927-1937)During the Twenties and Thirties of last century within the Spanish anarchic movement took hold a new individualistic trend which adopted the sexual free- dom problem as one of its main themes. Between 1927 and 1937 two journals, “Ética” at first and then “Iniciales”, which followed, were the tools for debating, spreading and building this new sexual ethics, based on eugenism, neomalthusia- nism and naturism.